A CRITICAL DISCOURSE ANALYSIS ON TAYLOR SWIFT’S ANTI-HERO MUSIC VIDEO - Karla Auria Galeon; Chessa Pae Faustino (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2023)
Music videos, as an integral part of pop culture, are audio-visual vehicles of communication. Thus, the need for its analysis to examine intended meaning/s of the artist is crucial particularly in the field of semiotics. In this study, Taylor Swift’s Anti-Hero music video was investigated through Social Semiotic Theory and Semiotic Theory; its denotative and connotative signs, and the ensuing myth are identified and interpreted through qualitative analysis, particularly content analysis. The elements that Swift utilized in her music video are imagery and symbolism, as well as allusions and intertextuality to her previous works. The overarching theme of Swift’s nightmares and internal thoughts are elaborated through reminiscing her past actions and experiences, declarations of accountability, paranoia, inevitability and aftermath of human demise, and other personal struggles. Swift alludes to various social issues, namely misogyny, politics, and mental health issues which strongly reflects the status quo. Furthermore, the music video contains hints and clues considered as easter eggs by fans to reference and hint at past and future projects respectively. Swift’s Anti-Hero presents personal shortcomings and struggles in a way that is both humorous and thought-provoking to the audience.